Lincomycin, cultivation of producing strains and biosynthesis - Spízek, J; Rezanka, T (Applied microbiology and biotechnology, 2004)
Lincomycin and its derivatives are antibiotics exhibiting biological activity against Gram-positive bacteria. The semi-synthetic chlorinated lincomycin derivative is used in clinical practice. The chemical structure of lincosamide antibiotics, cultivation of producing strains and analytical procedures used for separation and isolation of these compounds are described in this review. Biosynthesis of lincomycin and related compounds and its genetic control are briefly discussed.
Keywords: Streptomyces; biomasa; Citric Acid; Genes, Bacterial; Biomass; multigenová rodina; Lincomycin; linkomycin; chromatografie; bakteriální geny; Chromatography; časové faktory; kyselina citronová; Time Factors; Gene Order; glukosa; pořadí genů; Glucose; Multigene Family